Computer design of diffractive optics - Soifer, V. A. (Woodhead Publishing series in electronic and optical materials ;, 2013)
Diffractive optics involves the manipulation of light using diffractive optical elements (DOEs). DOEs are being widely applied in such areas as telecommunications, electronics, laser technologies and biomedical engineering. Computer design of diffractive optics provides an authoritative guide to the principles and applications of computer-designed diffractive optics. The theoretical aspects underpinning diffractive optics are initially explored, including the main equations in diffraction theory and diffractive optical transformations. Application of electromagnetic field theory for calculating diffractive gratings and related methods in micro-optics are discussed, as is analysis of transverse modes of laser radiation and the formation of self-replicating multimode laser beams. Key applications of DOEs reviewed include geometrical optics approximation, scalar approximation and optical manipulation of micro objects, with additional consideration of multi-order DOEs and synthesis of DOEs on polycrystalline diamond films. With its distinguished editor and respected team of expert contributors, Computer design of diffractive optics is a comprehensive reference tool for professionals and academics working in the field of optical engineering and photonics. Explores the theoretical aspects underpinning diffractive opticsDiscusses key applications of diffractive optical elementsA comprehensive reference for professionals and academics in optical engineering and photonics.